Perbandingan Efisiensi Biaya Berdasarkan Perhitungan Struktur Pada Kerangka Atap Menggunakan Baja Ringan dan Baja Berat Dengan Bentang 14.5 M - Faizal Mahmud; Kukuh Wisnuaji Widiatmoko (Jurnal Teknik Sipil Unaya, 2022)
Structural analysis of lightweight steel roof truss and heavy steel roof truss (conventional) spans 14.5 m in terms of cost and work efficiency. The roof truss studied consisted of: truss distance of 1.5 m for mild steel, and 3.75 m for heavy steel, with a slope angle of 20°, the roof covering on both uses sheet metal tile. Modeling and calculating this of level damages (ratio) and roof truss deflection use SAP 2000. The Budget Plan is calculated based on the PUPR Ministerial Regulation 28-2016 using the 2021 unit price. From this research, the results obtained are reduction percentage in price per unit meter2 of light steel roof truss. against heavy steel roof trusses reached 42.84%. Both models (light steel and heavy steel) have ratio and deflection values that are within safe limits, namely the ratio of 0.850114 for mild steel, 0.733239 for heavy steel, and deflection of 0.00054 for mild steel, 0.000075 for heavy steel.